Formamidinium‐Based Lead Halide Perovskites: Structure, Properties, and Fabrication Methodologies - Li, Yang; Liu, Fang Zhou; Waqas, Muhammud; Leung, Tik Lun; Tam, Ho Won; Lan, Xiao Qi; Tu, Bao; Chen, Wei; Djurišić, Aleksandra B.; He, Zhu Bing (Small methods, 2018)
Formamidinium (FA)‐based perovskites exhibit great potential for photovoltaics since they enable the achievement of power conversion efficiency (PCE) over 22%. The bandgap of FA‐based perovskite is lower than that of the methylammonium‐based one, while the larger ionic radius and dual‐ammonia group of FA ions restrain their movement in close‐packing [PbI6]4− cages, leading to improved stability. Here, the structure and properties of FAPbI3− and FA‐based mixed cation perovkites are discussed. In particular, the issues of polymorphism and stabilization of the desired low‐bandgap crystal phase of FAPbI3 are considered. FAPbI3 exhibits polymorphisms with a photovoltaically unfavorable δ‐phase that is stable at room temperature, and, thus, it is difficult to prepare continuous and compact FAPbI3 with the desired crystal structure, namely, the pure α‐phase. Hence, overcoming the limitations of phase transitions is the critical issue in obtaining high‐quality FA‐based perovskite films, which are a prerequisite for solar cells with high PCEs. Here, the focus is on the fabrication methods of FA‐based perovskite films, namely, additive engineering, intermolecular exchange, interfacial engineering, and chemical vapor deposition. A comprehensive overview of the fabrication methodology for the FA‐based perovskite films is provided to facilitate understanding of the underlying mechanisms. Formamidinium (FA)‐based perovskites dominate perovskite solar cells with conversion efficiency over 20%. However, phase transitions trouble the fabrication of high‐quality peroskite films, and hence it is critical to overcome this limitation. By a comprehensive understanding of coordination chemistry and interface interactions, such successful methods are reviewed systematically and logically, bringing a full scope of its methodology.